PENGARUH HUBUNGAN PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (STUDI EMPIRIS PADA MANULIFE FINANCIAL INDONESIA). - Denny Asmas (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
This  research  was  conducted  to  find  out  the  influence  of  managerial  performance  against  budget  participation,  the  influence  of  participation  in  managerial  performance  increase  budget  through  organizational  commitment,  the  influence  of  organizational  commitment  on  performance  of  managerial,  as  well  as  to  know  the  influence  of  the  participation  of  the  budget  and  organizational  commitment  affect  managerial  performance  on  PT  Asuransi  Jiwa  Manulife  Indonesia  or  Manulife  Financial  simultaneouslyIn  collecting  research  data  using  the  intrument  research.  Intrument  research  made  by  the  researchers  tested  the  validity  and  reabilitasnya.  Instrument  can  be  kuestionerresearch,  observation  and  interview.  The  data  collected  was  analyzed  further  by  using  statistical  analysis  of  deskriftif  and  inferensial  statistical  analysis  of  Researchers  using  inferensial  because  research  conducted  on  random  samples  taken  from  a  population.The  results  of  hypothesis  testing  of  research  it  can  be  concluded  that  the  partial  Participation  in  budget,  a  budget  with  participation  of  organizational  commitment  as  avariable  interveningnya,  influential  organization  significant  positive  Commitment  towards  managerial  performance  at  manulife  financial.  Simultaneously,  participation  and  commitment  of  the  Organization's  budget  a  significant  positive  effect  on  performance  in  managerial  Manulife  Financial  with  proven  significant  values  0.000  is  uji_F  α  <.Keywords:  participation  budget,  organizational  commitment  and  managerial  performance